What sample preparation should be chosen for targeted MS monoclonal antibody quantification in human serum?. (17th May 2018) - Vialaret, Jérôme; Broutin, Sophie; Pugnier, Célia; Santelé, Sophie; Jaffuel, Aurore; Barnes, Alan; Tiers, Laurent; Pelletier, Laurent; Lehmann, Sylvain; Paci, Angelo; Hirtz, Christophe
Aim: Monoclonal antibody-based treatment of cancer has been established as one of the most successful therapeutic strategies.Materials & methods: In this work, we developed a workflow based on an automated protein-A capture and LC–MS/MS analysis to quantify bevacizumab on patient serum during treatment. This analytical approach was fully validated and compared with a commercially available Monoclonal antibody-based treatment preparation (nanosurface and molecular-orientation limited kit).Results: The analytical comparison of the two preparative workflows based on protein-A capture gave similar results with a better lower limit of quantification for the nanosurface and molecular-orientation limited kit (0.26986 vs 1.9565 μg/ml).Conclusion: LC–MS/MS has clear advantages compared with ELISA when considering method development time, multiplexing capacities and absolute quantification with internal standardization. Graphical abstract: